Design of 4-DOF Voice Coil Motor with Function of Reducing Laser Geometrical Fluctuations - Chien-Sheng Liu; Yu-Cheng Wu; Yu-Jie Lan (Actuators, 2021)
In order to improve the quality of the laser and shorten the optical path of the fast steering mirror (FSM) laser compensation system, this paper proposes a four-degrees-of-freedom (4-DOF) voice coil motor (VCM) with the function of reducing laser geometrical fluctuations. The feature of this paper is the combination of a DC brushed spindle motor and the proposed 4-DOF VCM. A diffuser is installed on the shaft of the DC brushed motor for suppressing the laser speckle. The proposed 4-DOF VCM is combined with a laboratory-designed mirror set, controlling the laser direction to compensate for laser fluctuations. The proposed actuator was designed and verified by using the commercial CAD software SolidWorks and finite element analysis (FEA) software ANSYS. A mathematical model was built to simulate the dynamic response of the proposed 4-DOF VCM in MATLAB Simulink.